Agroforestry field laboratory a potential carbon storage and sequestration of Claveria, Misamis Oriental, the Philippines - Palma, Richmund A. (Philippine Journal of Science, 2024)
Biomass and carbon sequestration of different land uses in the USTP Claveria, Claveria, Misamis Oriental, the Philippines, were determined in this study. Five nested plots were established throughout the 25-ha AFL for data collection. All trees inside the nested plots were identified and measured to determine the species and biomass. The carbon stock was determined using allometric equations and conversion values. The result showed that trees stock a large amount of biomass and carbon per unit area. The accumulated carbon stocks of trees ranged from 131.69–327.97 t ha–1. It gives important information in the application related to the development of the campus, valuation, assessment, and accreditation.